Optimal Operation and Control Design of DC Arrester for Renewable Energy Transmission - Feng, Yue; Li, Kaiping; Gao, Min; Liu, Yaozhang; Li, Xiaojun; Zhu, Jiawei (Frontiers in Energy Research, 2021)
The trip probability of transmission line in the face of lightning stroke is increasing under complex weather when renewable energy connects to the power grid. Besides, line arrester plays an essential role in reducing lightning damage and economic losses, in which DC reference voltage is a critical parameter to evaluate line arresters. Hence, a set of on-site DC test system of transmission line arresters is developed to complete DC reference voltage test in this paper. In addition, the output DC voltage of the test system is continuously adjustable (0-200 kV) while its rated power and the maximum output current are 400 W and 2 mA, respectively. Furthermore, the system is powered by a lithium battery instead of 220/380 V AC energy source. Meanwhile, Bluetooth remote control module is used to effectively ensure the safety of test personnel. Moreover, this system accomplishes DC reference voltage tests without removing line arresters on site, which is conducive to improving maintenance efficiency and economic benefits.